Daniel X, the manga. 3 - Patterson, James, 1947- (Patterson, James, 1947- Daniel X novels, 2012)
"Using his incredible abilities, Daniel X continues to track down intergalactic criminals bringing their alien brand of evil to Earth! The next target on the List is Phosphorius Beta, an explosive demon of fire with a legion of flame-weaving henchmen. Even though his own powers have grown since taking down Number 5, the only chance Daniel has of beating this ancient demon is to go back in time to the Dark Ages and destroy Beta before his blistering reign has a chance to even begin. But can Daniel X take the heat? Or will the alien hunter finally get burned?"--P. [4] of cover.